Proposal for the application of ICE and BIM sessions to increase productivity in construction - Quiso, E. (2021)
Several studies have shown that the main problem in the construction industry is low productivity. Therefore, this study focuses on developing a proposal through a methodology that can increase productivity in the construction of buildings. The proposed methodology is Virtual Design and Construction (VDC), which has 4 pillars: Building Information Modeling (BIM), Integrated Concurrent Engineering (ICE), metrics and Project Production Management (PPM). However, the article mainly develops BIM and ICE sessions. In addition, in the ICE sessions, "work executors"will be added, so that the information is fed back by both parties, specialist engineers and work executors. Finally, the proposal will be applied in a multi-family building project in the city of Lima - Peru, in order to obtain improvement results.